Vanillylacetone attenuates NLRP3 inflammasome mediated immune responses in murine bone marrow derived macrophages via NLRP3 alkylation. (January 2020) - Kim, Han-Bi; Kwon, Sang-Chul; Sun, Xiao; Akther, Mahbuba; Han, Jun-Hyuk; Kim, Tae-Yeon; Kang, Tae-Bong; Lee, Kwang-Ho
Graphical abstract: Highlights: This is the first report of inhibition of inflammasome activation by vanillylacetone. Vanillylacetone (VA) inhibited NLRP3 inflammasome activation via NLRP3 alkylation. VA reduced IL-1β and neutrophil recruitment in peritoneal lavage fluid in mice. VA can be a therapeutic agent against NLRP3 inflammasome-associated diseases. Abstract: Vanillylacetone (VA) is widely used as a food additive owing to its sweet flavour. In this study, we have reported for the first time that VA has an inhibitory role in inflammasome activation. We examined the effect of VA on inflammasome activation and investigated the underlying physiological mechanisms. We verified that VA suppresses IL-1β and caspase-1 secretion, induced by NLRP3 inflammasome activation, in lipopolysaccharide (LPS)-primed bone marrow-derived macrophages. ASC speck formation and oligomerization were also attenuated by VA treatment. VA potentially inhibits NLRP3 inflammasome activation via NLRP3 alkylation. The in vivo efficacy of VA on NLRP3 inflammasome activation was examined in an MSU-induced murine peritonitis model. IL-1β and neutrophil recruitment in peritoneal lavage fluid was significantly reduced by VA treatment, thus suggesting that VA could potentially be used as a therapeutic agent against NLRP3 inflammasome-associated diseases.